FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TANI PADI CIHERANG DI DESA TEBING TINGGI KABUPATEN SERDANG BEDAGAI - Saragih, M.Sc, Faoeza Hafiz (JURNAL AGRICA, 2020)
Up to now, paddy farmers as farm managers have not received the expected results and income from both the farmers themselves and the government. This study aims to determine the factors that influence rice farming income in Tebing Tinggi Village, Deli Serdang Regency. The reason for choosing this location is because this village is the recipient of seed aid from SLPTT where there are 160 farmers using Ciherang seeds. The number of farmers sampled in this study were 40 farmers and the variables tested were labor costs, phonska fertilizer costs, SP fertilizer costs, KCl fertilizer costs, pesticide costs, land area, urea fertilizer costs, ZA fertilizer costs and seed prices. The results showed that feasibility of farm bussiness has R/C ratio was 3,28 its mean the farm business was feasible labor costs, KCl fertilizer costs and urea fertilizer costs had a significant effect on rice farming income, while other variables had no effect. Fertilizer subsidies and seed assistance are government policies that greatly relieve farmers in financing their farming business so that this policy must continue to be carried out and monitored in its implementation in an effort to increase the income of rice farmers.